1989
DOI: 10.1246/cl.1989.213
|View full text |Cite
|
Sign up to set email alerts
|

Excessively Copper Ion-exchanged ZSM-5 Zeolites as Highly Active Catalysts for Direct Decomposition of Nitrogen Monoxide

Abstract: Repeated ion exchange of the ZSM-5 zeolite using aqueous copper(II) acetate solution was found to bring about excess loading of copper ions above 100% of exchange level. The catalytic activities of the resulting Cu-ZSM-5 zeolites for direct decomposition of nitrogen monoxide were very high and increased with increasing exchange level. The activity did not decrease even after 30 h of continuous service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(117 citation statements)
references
References 1 publication
4
111
0
2
Order By: Relevance
“…K-ZSM-5 (Si/Al = 31, ExxonMobil Chemical) was put in the Na + form and overexchanged with Cu 2+ according to the method of Iwamoto et al [56]. One gram of Na-ZSM-5 was ion-exchanged in 25 ml of a 0.01 M Cu(CH 3 CO 2 ) 2 · H 2 O solution at ambient temperature for 24 h. This procedure was repeated three times.…”
Section: Samplesmentioning
confidence: 99%
“…K-ZSM-5 (Si/Al = 31, ExxonMobil Chemical) was put in the Na + form and overexchanged with Cu 2+ according to the method of Iwamoto et al [56]. One gram of Na-ZSM-5 was ion-exchanged in 25 ml of a 0.01 M Cu(CH 3 CO 2 ) 2 · H 2 O solution at ambient temperature for 24 h. This procedure was repeated three times.…”
Section: Samplesmentioning
confidence: 99%
“…Selective catalytic reduction (SCR) of NOx by NH3 is an efficient technology for controlling NOx emissions [1]. Ever since Iwamoto et al [2] reported that the Cu-ZSM-5 catalyst showed high activity of selective catalytic reduction of NOx, much work has been performed to explore the catalytic properties of those catalysts, especially for on-road applications [3,4]. The utility of ZSM-5 as catalyst supports derives significantly from their remarkable ion-exchange capacity [5].…”
Section: Introductionmentioning
confidence: 99%
“…For the decomposition of NO, it has been indicated that Cu-ZSM-5 is the most active catalyst [8][9][10]. Unfortunately, over-exchanged capacity of Cu-ZSM-5 is active only in a limited interval of temperatures and in the absence of O 2 [11].…”
Section: Introductionmentioning
confidence: 99%